Textbook of orthopaedics - Ebnezar, John (Jaypee Brothers Medical Publishers, 2006)
This uniquely outstanding text provides the core knowledge with multicolour artwork, about 1100 mind-boggling colour diagrams have been especially created to explain anatomy. It includes quick short summaries, anecdotes and recaps with flow charts, clinical photographs and typical X-rays of important orthopaedic conditions. A consistent organization by body region, summary tables and detailed artwork makes this reference perfect for quick review.